Component‐based permission management of Android applications. (15th July 2019) - Fu, Jiaojiao; Zhou, Yangfan; Wang, Xin
Summary: Most Android applications include third‐party libraries (3PLs) to make revenues, to facilitate their development, and to track user behaviors. 3PLs generally require specific permissions to realize their functionalities. Current Android systems manage permissions in app (process) granularity. As a result, the permission sets of apps with 3PLs (3PL‐apps) may be augmented, introducing overprivilege risks. In this paper, we firstly study how severe the problem is by analyzing the permission sets of 27 718 real‐world Android apps with and without 3PLs downloaded in both 2016 and 2017. We find that the usage of 3PLs and the permissions required by 3PL‐apps have increased over time. As a result, the possibility of overprivilege risks increases. We then propose Perman, a fine‐grained permission management mechanism for Android. Perman isolates the permissions of the host app and those of the 3PLs through dynamic code instrumentation. It allows users to manage permission requests of different modules of 3PL‐apps during app runtime. Unlike existing tools, Perman does not need to redesign Android apps and systems. Therefore, it can be applied to millions of existing apps and various Android devices. We conduct experiments to evaluate the effectiveness and efficiency of Perman. The experimental results verify that Perman is capable of managing permission requests of the host app and those of the 3PLs. We also confirm that the overhead introduced by Perman is comparable to that by existing commercial permission management tools.